Prothrombin Activation Fragment 1 + 2 and Thrombin Antithrombin III Complexes in Patients with Angina Pectoris: Relation to the Presence and Severity of Coronary Atherosclerosis - Kienast, J; Thompson, S G; Raskino, C; Pelzer, H; Fechtrup, C; Ostermann, H; Loo, J van de (Thrombosis and Haemostasis, 1993)
Plasma levels of the prothrombin activation fragment 1 + 2 (F 1 + 2) and of thrombin antithrombin III complexes (TAT) were determined in 225 patients with angina pectoris undergoing coronary angiography. Oral anticoagulant therapy was associated with a marked reduction in mean Fl + 2 (0.63 vs 1.62 nmol/l, p <0.0001) and TAT levels (1.65 vs 2.23 μg/1, p <0.0001). Omitting patients on oral anticoagulants, TAT values showed a positive association with patients’ age (r = 0.18; p = 0.01) and were slightly higher in patients with a history of myocardial infarction than in those without (2.47 vs 2.11 <g/l; p = 0.06). Both Fl + 2 and TAT levels were increased in patients with angiographically verified coronary atherosclerosis as compared to patients with angina and angiographically normal coronaries (Fl + 2: 1.76 vs 1.36 nmol/1, TAT: 2.35 vs 2.00 μg/1; p-values after adjusting for age, sex and past history of myocardial infarction 0.06 and 0.11 respectively). However, no graded relationship between Fl + 2 or TAT values and severity of atherosclerosis was observed. This study provides suggestive evidence that a procoagulant state exists in patients with angina pectoris and coronary atherosclerosis. Its relevance in predicting coronary ischaemic events needs to be studied prospectively.